2014
DOI: 10.1371/journal.pone.0092730
|View full text |Cite
|
Sign up to set email alerts
|

Internal Jugular Vein Blood Flow in Multiple Sclerosis Patients and Matched Controls

Abstract: The aim of the study was to investigate the Internal Jugular Veins dynamics using contrast enhanced ultrasonography in Multiple Sclerosis patients, clinically isolated syndrome patients and healthy controls. Contrast enhanced ultrasonography imaging of the Internal Jugular Vein was performed in fifty-eight patients with Multiple Sclerosis, seven clinically isolated syndrome patients and in thirteen healthy controls. Time-intensity curves were quantified using a semi-automated method and compared with clinical … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
23
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 21 publications
(24 citation statements)
references
References 45 publications
1
23
0
Order By: Relevance
“…This work is one of the recent studies concerning the relations among the main cerebral venous outflow routes, their disorders, and the occurrence of neurological diseases (10,17,19,28,29,34).…”
Section: Resultsmentioning
confidence: 99%
“…This work is one of the recent studies concerning the relations among the main cerebral venous outflow routes, their disorders, and the occurrence of neurological diseases (10,17,19,28,29,34).…”
Section: Resultsmentioning
confidence: 99%
“…Almost 80% of MS patients showed a delayed clearance time in at least one IJV [53]. This result was mirrored by Mancini et al by the means of contrast enhanced ultrasound, which demonstrate a significant reduction of clearance time in the IJV of MS patients respect to healthy controls, when injected with standardized contrast micro bubbles [54]. Interestingly these Authors also found a significant inverted correlation between the delayed IJV contrast clearance and the level of disability, since slower flow corresponded to higher expanded disability severity score.…”
Section: Cerebral Venous Drainage Consequences Of Ijv Pathologymentioning
confidence: 72%
“…7 On the other hand, by using quantitative Doppler ultrasound measurements of the venous blood flow, several studies showed global venous hemodynamic differences associated with MS. A contrast-enhanced ultrasonography study showed heterogeneity in the venous outflow system consistent with slow washout dynamic. 22 All the aforementioned changes have been previously described as part of chronic cerebrospinal venous insufficiency (CCSVI) condition which is characterized by anomalies of the main extracranial cerebrospinal venous routes that interfere with normal blood outflow. 2 Higher prevalence of CCSVI has been reported not only in MS patients, but also in Parkinson disease, 24 and Meniere disease.…”
Section: Discussionmentioning
confidence: 99%